2020
DOI: 10.3892/etm.2020.9381
|View full text |Cite
|
Sign up to set email alerts
|

Biochanin A alleviates gingival inflammation and alveolar bone loss in rats with experimental periodontitis

Abstract: Biochanin A (BA) is an organic compound produced by Trifolium pretense and Arachis hypogaea with anti-inflammatory and antioxidative effects. The aim of the current study was to evaluate the effects of BA on gingival inflammation and alveolar bone destruction in rats with experimental periodontitis. Experimental rats (n=25) were distributed equally into five groups: i) Healthy control (control) group; ii) experimental periodontitis (ligation) group; and iii) and ligation plus low, medium and high dose of BA (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The results for biochanin A are also interesting. It appears that treatment with biochanin A inhibited inflammation, regulated the unbalanced oxidative stress response and improved alveolar bone loss in periodontitis [ 47 ]. Sin et al [ 48 ] showed that flavonols were more potent inhibitors than flavones/isoflavones.…”
Section: Resultsmentioning
confidence: 99%
“…The results for biochanin A are also interesting. It appears that treatment with biochanin A inhibited inflammation, regulated the unbalanced oxidative stress response and improved alveolar bone loss in periodontitis [ 47 ]. Sin et al [ 48 ] showed that flavonols were more potent inhibitors than flavones/isoflavones.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, all rats ( n = 5 per group) were anesthetized with 6% sevoflurane, followed maintain anesthesia with 4% sevoflurane during the experimental procedures. And blood was drawn by cardiac puncture 35 . After the cardiac puncture, the rats were euthanized by CO 2 inhalation followed by cervical dislocation immediately.…”
Section: Methodsmentioning
confidence: 99%
“…And blood was drawn by cardiac puncture. 35 After the cardiac puncture, the rats were euthanized by CO 2 inhalation followed by cervical dislocation immediately. The maxillary jaws and gingiva were harvested.…”
Section: Ovx-periodontitis Rat Model and Study Designmentioning
confidence: 99%
“…In rat midbrain neuron-glia cultures, BCA has been reported to be effective not only in reducing lipopolysaccharide (LPS)-induced reductions in dopamine uptake and the number of dopaminergic neurons, but also in inhibiting lipopolysaccharide-induced microglial activation of tumour necrosis factor, nitric oxide and superoxide production by microglia [35]. It can also effectively alleviate gingival inflammation, a common oral disease, in rats by inhibiting TNF-ɑ, IL-1β, ROS and elevating OCN a and Nrf2 levels [36].…”
Section: Anti-inflammatory Functionmentioning
confidence: 99%